DC Microgrid Network Design For Household DC Load Management - Handayani, Fitri (International Journal of Engineering and Emerging Technology; Vol 6 No 2 (2021): July - December 2021, 2022)
Pembangkit Listrik Tenaga Surya or called PLTS Microgrid is one solution to meet the needs of electricity. Microgrid is a system designed by utilizing 2 sources of electrical energy, one of the energy sources can be obtained from PV with a PLN grid source. In this system, the management is carried out with different treatments on each load. For lights and fans, the load is regulated by the PIR sensor.  both will light up when the sensor detects the presence of humans. Meanwhile, the charger itself can be used at any time. The microgrid system can work with a switching process for 1 second with the condition that when the voltage on the battery is less than 12,1 V, the system will receive a supply from PLN. PV is capable of charging the battery with a voltage in the morning and afternoon of 18V with the output voltage generated by the Buck Boost Converter still not reaching the set point, which is still at 12,5 v until 13 V. This is due to the control on the hardware still not working perfectly. The use of PIR sensors to regulate load ignition can reduce excessive load usage. In this system the current sensor readings are not good when integration testing is carried out, so the load power that is read does not match the power in the plan, which is 8 W while in the planning it is 26 W.